“Northern Balance” and the Conditions of Norway’s Participation in NATO During the Cold War Era - D. A. Talagaeva (Vestnik MGIMO-Universiteta)
The article is dedicated to the problem of defining the term “Northern balance” as a factor of stability and interaction in the north of Europe, as well as the balance of Soviet and US interests in this region. Particular attention is paid to the analysis of practical grounds for such a definition, primarily to the peculiarities in the Northern European foreign policy in relation to NATO. Besides, the article focuses on Norwegian foreign policy and the terms of the country’s membership in the North-Atlantic alliance.